Respiratory mucosal immune memory to SARS-CoV-2 after infection and vaccination - Mitsi, E; Diniz, MO; Reiné, J; Collins, AM; Robinson, RE; Hyder-Wright, A; Farrar, M; Liatsikos, K; Hamilton, J; Onyema, O; Urban, BC; Solórzano, C; et al. (Springer Nature, 2023)
Respiratory mucosal immunity induced by vaccination is vital for protection from coronavirus infection in animal models. In humans, the capacity of peripheral vaccination to generate sustained immunity in the lung mucosa, and how this is influenced by prior SARS-CoV-2 infection, is unknown. Here we show using bronchoalveolar lavage samples that donors with history of both infection and vaccination have more airway mucosal SARS-CoV-2 antibodies and memory B cells than those only vaccinated. Infection also induces populations of airway spike-specific memory CD4+ and CD8+ T cells that are not expanded by vaccination alone. Airway mucosal T cells induced by infection have a distinct hierarchy of antigen specificity compared to the periphery. Spike-specific T cells persist in the lung mucosa for 7 months after the last immunising event. Thus, peripheral vaccination alone does not appear to induce durable lung mucosal immunity against SARS-CoV-2, supporting an argument for the need for vaccines targeting the airways.